Diabetic ketoacidosis and cognitive impairment in children and adolescents - K. Sh. Magomedova; Yu. V. Bykov; V. A. Baturin (Бюллетень сибирской медицины, 2023)
The aim of the literature review was to highlight modern scientific sources on the formation and clinical manifestations of cognitive impairment in children and adolescents with type 1 diabetes mellitus (DM) after diabetic ketoacidosis (DKA). Type 1 DM is one of the most prevalent endocrine disorders in childhood and adolescence. DKA is the most common acute complication of type 1 DM that may cause cognitive impairment. Cerebral edema is the main cause of cerebral vascular insufficiency in patients with DKA. However, the mechanisms underlying the development of cognitive dysfunction in DKA have not been fully elucidated.The leading hypotheses include development of neuroinflammation, oxidative stress, disruption of neurogenesis, and neurodegeneration. Hypoxic – ischemic injury and changes in the brain neuroanatomy may also cause cognitive dysfunction. Disruption of some brain structures has been reported after DKA episodes, primarily affecting the white matter. Clinical studies in the pediatric population support the presence of a correlation between the severity and frequency of DKA and the severity of cognitive impairment. Cognitive dysfunction in children and adolescents after a DKA episode can manifest through decreased attention, impaired memory and executive function, and reduced IQ. The earliest possible diagnosis of cognitive impairment in pediatric patients with symptoms of DKA in the context of type 1 DM can improve the treatment prognosis for this endocrinopathy.